Construction of two Neurospora crassa Lambda ZapII-cDNA libraries - K. Hoang-Van; C. Rossier; G. Turian (Fungal Genetics Reports, 1991)
In the presence of the anti-microtubule agent benomyl, N. crassa synthesizes and secretes a major 60 kDa protein in the culture medium. This protein is absent in untreated cells (Rossier et al. 1989. Eur. J. Cell Biol. 50:333-339). To clone the gene coding for the 60 kDa protein and to unravel its function, we have constructed a cDNA library from benomyl-treated cells ("benomyl" cDNA library). A second cDNA library was constructed from untreated cells in order to clone genes coding for cytoskeletal proteins ("standard" cDNA library).